UV Radiation, not European Ancestry, Explains States’ Cognitive Performance in Brazil and USA - R. León, Federico (2022)
A debate in Mankind Quarterly positing racial categorization of populations vis-à-vis biological effects of UV radiation was based on data from a single country, used absolute latitude instead of UV radiation, and limited the analysis to path analysis. To overcome limitations of the studies, we utilized measurements of UV radiation for 26 Brazilian and 48 USA states instead of absolute latitude and performed seemingly unrelated regressions in addition to path analysis. NAEP scores and infectious disease rate were collected in USA and PISA scores and infant mortality in Brazil. Significant cognitive effects of European ancestry were replicated, but showed spuriousness, disappearing when the effects of UV radiation were controlled. Our evidence strongly suggests that UV radiation is a consistent antecedent of cognitive ability directly and through income in the USA and Brazil and through infant mortality in Brazil, whereas European ancestry only influences cognitive ability positively by reducing infectious diseases in the USA or infant mortality in Brazil. The between-country consistency of our findings compensates for methodological weaknesses that took place especially in the Brazil study. Psychologists and economists should be aware of these findings to avoid making erroneous inferences based on genetic or cultural variables.